Functional recovery guided by an electrospun silk fibroin conduit after sciatic nerve injury in rats. (22nd October 2012) - Park, Sook Young; Ki, Chang Seok; Park, Young Hwan; Lee, Kwang Gill; Kang, Seok Woo; Kweon, Hae Yong; Kim, Hyun Jeong
Abstract The aim of this study was to evaluate the regenerative capacity of a newly developed nerve guidance conduit using electrospun silk fibroin (SFNC) implanted in a 10‐mm defect of the sciatic nerve in rats. After evaluating the physical properties and cytocompatibility of SFNC in vitro, rats were randomly allocated into three groups: defect only, autograft and SFNC. To compare motor function and abnormal sensation among groups, ankle stance angle (ASA) and severity of autotomy were observed for 10 weeks after injury. Immunostaining with axonal neurofilament (NF) and myelin basic protein (MBP) antibodies were performed to investigate regenerated nerve fibres inside SFNC. ASA increased significantly in the SFNC group at 1, 7 and 10 weeks after injury compared to the defect only group (p < 0.05). At one week, mean ASA of the SFNC group was significantly higher than that of the autograft group (p < 0.05). Onset and severity of autotomy decreased significantly in the SFNC group compared to other groups (p < 0.05). Autotomy in the SFNC group started at 4 weeks and maximally reached toe level. However, the defect only and autograft groups first showed autotomy at 2 and 1 weeks following injury, respectively, and then reached the sole level. Well myelinated nerve fibres stained with NF and MBP were found inside SFNC. In conclusion, SFNC could be helpful in restoring motor function and preventing abnormal sensations after nerve injury. Copyright © 2012 John Wiley & Sons, Ltd.